Spontaneous ureteral rupture caused by iliac aneurysm: a case report - Hirotaka Sato; Soki Kurumisawa; Tsutomu Saito; Koji Kawahito (Surgical Case Reports, 2018)
Abstract Background Rupture of the ureter with extravasation resulting from an iliac aneurysm is extremely rare. Herein, we report a case of ureteric rupture with urinary extravasation secondary to an iliac aneurysm. Case presentation An 80-year-old man was admitted to our hospital for sudden onset of severe abdominal pain. Contrast-enhanced computed tomography demonstrated a large left internal iliac aneurysm (6.5 cm in diameter) and a ureteric rupture with leakage of contrast media from the left ureter, indicating a spontaneous ureteral rupture. The patient was treated with placement of a ureteral double-J stent under endoscopic and X-ray fluoroscopic guidance and endovascular aortic repair. His postoperative course was uneventful and he was discharged on postoperative day 20. A computed tomography scan at 2 weeks after surgery showed no contrast extravasation from the ureter or end leak. Conclusion Combination treatment with ureteral and endovascular stenting is effective in avoiding aneurysmal rupture and the serious consequences of a ureteral rupture, which include a perinephric or retroperitoneal collection, abscess formation, subsequent urosepsis, and graft infection.